2015
DOI: 10.1183/13993003.00456-2015
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial hypertension or left heart disease with pulmonary hypertension? Toward noninvasive clarity, but time for a new paradigm

Abstract: @ERSpublications PAH or left heart disease with PH? Perspective on group 1 and 2 PH differentiators and a call for a unified approach http://ow.ly/OtRxU Widespread availability of Doppler echocardiography, combined with increasing community awareness of pulmonary arterial hypertension (PAH) as an important and treatable disease, results in frequent referral of patients with suspected PAH to tertiary pulmonary hypertension centres. While this state of affairs is laudable, it does result in substantial numbers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…6 The National Heart, Lung, and Blood Institute Pulmonary Vascular Disease Phenomics (PVDomics; RFA-HL-14-027) 7 and other groups 8 are evaluating better ways to phenotype PH patients. The use of molecular biomarkers is one way to better phenotype these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The National Heart, Lung, and Blood Institute Pulmonary Vascular Disease Phenomics (PVDomics; RFA-HL-14-027) 7 and other groups 8 are evaluating better ways to phenotype PH patients. The use of molecular biomarkers is one way to better phenotype these patients.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Predicting prognosis in PH has been limited, as classifying and phenotyping patients with PH are largely 'based on a relatively simple combination of patient characteristics and hemodynamics'. 6 The National Heart, Lung, and Blood Institute Pulmonary Vascular Disease Phenomics (PVDomics; RFA-HL-14-027) 7 and SUMMARY AT A GLANCE S100A12 serum levels are elevated in patients with pulmonary hypertension and they are associated with increased mortality rates. These findings show that the S100A12 biomarker has a major role to play in determining the prognosis of pulmonary hypertension patients, and they would enrich deep phenotyping efforts in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the PAH phenotype, PH-HFpEF is characterized by specific demographic, clinical, and echocardiographic features, including older age, female gender, hypertension, higher rate of atrial fibrillation, and metabolic syndrome (hyperlipidaemia, obesity, diabetes, and hypertension) [18] (Table 1). Many scores have been proposed so far [18][19][20][21][22][23][24], integrating features analysed from retrospective single centre studies; some have even suggested that simple clinical characteristics alone, without echocardiographic or hemodynamic data, were able to differentiate PH-HFpEF from PAH [25]. No score has been externally validated so far, but a similar approach has recently been proposed to assess HFpEF among patients with chronic heart failure.…”
Section: Pulmonary Hypertension: Pah and Ph-hfpefmentioning
confidence: 99%